Spontaneous iliopsoas hematoma in a trasfusion dependent β-thalassemia patient with hypersplenism: a case report - Padmakumari, Aishwariya; Talat, Mohammed; Soliman, Ashraf; De Sanctis, Vincenzo; Nashwan, Abdulqadir; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2018)
A 27-year-old married man with transfusion dependent β-thalassemia (TDT) complaining low back pain due to a spontaneous iliopsoas hematoma is reported. A magnetic resonance imaging (MRI) confirmed the diagnosis.The patient was managed conservatively. The mechanism of spontaneous iliopsoas hematoma was unclear, although tearing of muscle fibers, unrecognized minor trauma, low platelet count, secondary to hypersplenism, and severe liver iron overload, associated to abnormalities of clotting factors synthesis, were the suspected etiologies.  He showed a good response to treatment and was discharged home 11 days later. A new MRI, performed 7 months later, showed a complete resolution of hematoma. Although iliopsoas haematoma is an uncommon complication in patients with TDT, it should be considered in the differential diagnosis of a patient with back pain.